Trade Costs of Sovereign Debt Restructurings : Does a Market-Friendly Approach Improve the Outcome? - Asonuma, Tamon (IMF Working Papers; Working Paper, 2016)
Sovereign debt restructurings have been shown to influence the dynamics of imports and exports. This paper shows that the impact can vary substantially depending on whether the restructuring takes place preemptively without missing payments to creditors, or whether it takes place after a default has occurred. We document that countries with post-default restructurings experience on average: (i) a more severe and protracted decline in imports, (ii) a larger fall in exports, and (iii) a sharper and more prolonged decline in both GDP, investment and real exchange rate than preemptive cases. These stylized facts are confirmed by panel regressions and local projection estimates, and a range of robustness checks including for the endogeneity of the restructuring strategy. Our findings suggest that a country's choice of how to go about restructuring its debt can have major implications for the costs it incurs from restructuring.